SIMPUL-SIMPUL PENDIDIKAN DALAM SURAH AL ANFÂL DAN AL TAUBAH - Noorazmah Hidayati (Faculty of Ushuluddin and Humanities, 2013)
Today, concept of jihad disposed wrong to be understood. Jihad mean as a war, even must destroyed some people and creatures with in the name of Islam. As a consequence Islam refer to a terorist religion. This opinion must be corrected, because Islam is “rahmatan lil ‘alamiin”. In fact, in independent time jihad should be manifested to protect equitable and moral of humanbeing. This article describes some essences of education of jihad in surah al Anfâl and al Taubah with the result that every action will valued as jihad and humanbeing values will protected.